2001
DOI: 10.1046/j.1365-2044.2001.01870.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure of nurses on an intensive care unit

Abstract: References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
3
10
0
Order By: Relevance
“…[7] Similarly, another study looked into the radiation exposure to ICU nurses and found that the exposure was well below the permissible level. [8] The findings of our study have reiterated the results of these previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[7] Similarly, another study looked into the radiation exposure to ICU nurses and found that the exposure was well below the permissible level. [8] The findings of our study have reiterated the results of these previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…[6] However, the available literature on the extent of radiation exposure to ICU personnel is scarce and relates mainly to the level of scattered radiation within the ICU. [78] The conclusion of these studies is that the level of radiation exposure is extremely low and does not pose a hazard to ICU personnel. [78] None of these studies have considered the additional radiation exposure to ICU personnel involved in the management of critically ill patients in the Radiology Department.…”
Section: Introductionmentioning
confidence: 99%
“…Even after taking these additional sources of radiation exposure into account, we found that the cumulative radiation exposure was negligible. Similarly, another study looked into the radiation exposure to ICU nurses and found that the exposure was well below the permissible level [13]. The findings of our study have reiterated the results of these previous studies.…”
Section: Resultssupporting
confidence: 81%
“…The results indicated that the scattered radiation from X-rays exhibited a directional distribution, and the position where the technician stood affected the absorbed scattered radiation doses. As suggested by previous studies, the scattered radiation induced by X-ray exposure at a distance of 2 m was attenuated to background radiation levels (U.S. = 8.493 μGy per day) [26]. In the operating room, the measured background radiation dose was 0.06 μGyh í1 , i.e., the dose was 1.44 μGy per day.…”
Section: Discussionmentioning
confidence: 63%
“…As shown in Table 1, except for the X-ray examinations on the lumbar vertebrae and the perspective X-ray, the induced radiation was attenuated to background radiation levels. According to the provisions relevant to radiation safety, technicians should use portable lead shields when the patient stands within a range of 1 foot for the purpose of protecting the other patients and medical staff from unnecessary exposure and to reduce the radiation doses at work [26][27][28]. In this study, the experimental data provide professional knowledge on clinical radiation exposure levels for nurses in hospitals.…”
Section: Discussionmentioning
confidence: 99%